EVALUASI KESESUAIAN RESEP OBAT DM PADA PASIEN RAWAT JALAN TERHADAP FORMULARIUM NASIONAL DI RS ARAFAH ANWAR MEDIKA SUKODONO - Amarullah, Adinugraha; Jannah, Ananda Kurniatul; Fickri, Djelang Zainuudin; Anwari, Farida (Jurnal Insan Farmasi Indonesia, 2023)
Pharmaceutical services are services that are directly responsible to patients in relation to pharmacy. One of the factors that improve the quality of pharmaceutical services is prescription services. In the era of the National Health Insurance (JKN), prescriptions given to patients must refer to the National Formulary. If the prescription is not in accordance with the National Formulary, it will affect the quality of pharmacy installation services. Arafah Anwar Medika Hospital is one of the hospitals with a large number of patients diagnosed with diabetes and requires proper management of drug use. The purpose of this study was to determine the suitability and discrepancy of prescribing with the National Formulary for outpatient Diabetes Mellitus BPJS patients at Arafah Anwar Medika Sukodono Hospital. This research is a non-experimental descriptive study using quantitative research methods, purposive sampling technique with 384 data on all DM prescriptions for outpatient BPJS patients in 2021. not in accordance with FORNAS 2.86%. The conclusion is that a good pharmacy service quality will get a high percentage of prescription conformity with the National Formulary.